The Impact of Business Strategic Orientation on Innovation-Driven Mergers and Acquisitions: An Empirical Study - Zhuozhu Liu; Yiran Li; Zhaoyang Zhang; Rongying Zhao (Discrete Dynamics in Nature and Society)
The “innovation-driven” development approach plays a crucial role in transforming and developing current China’s national economy. Many innovation-driven mergers and acquisitions (M&As) emerge in the M&As activities of firms, and the acquiring firm’s business strategy of conducting innovation-driven M&As has drawn significant attention. To study the impact of business strategy on innovation-driven M&As, this paper adopts the probit model to conduct logistic regression analysis on the 223 M&As data samples, exploring which business strategy is inclined to perform innovation-driven M&As. The results show that prospective firms are more likely to conduct innovation-driven M&As. Besides, the firms that conduct prospective business strategies are more likely to have a higher innovation level than firms operating defensive business strategies. The innovation level plays the role of a mediator variable in the model of business strategies influencing innovation-driven M&As. This paper analyzes the innovation-driven motivation from the perspective of business strategy, enriching the research of M&A and offering a method to predict the possibility of innovation-driven M&A by measuring business strategy.